Integration of values and culture in Malay folklore animation - Abd Rahim, Normaliza; Awang Pawi, Awang Azman; Nik Muhamad Affendi, Nik Rafidah (Universiti Putra Malaysia Press, 2018)
This study focuses on the integration of values and culture in the Malay folklore animation. The objectives of the study are to rank and discuss the values and culture in the Malay folklore animation. The study adopts the values incorporated in the Malaysian National Education Philosophy (1996) to analyse the values and culture in the animations. The philosophy consists of 16 values, which are understood by all students in Malaysia. The values stated are related to the culture among the community, with 10 animations from The Kingfisher Stories. The results of the study reveal that the folklore Leader and Palm Tree contain the most number of values, that is, 10 values, while the folklore Crow, with two values, is ranked the lowest. The results show that values and culture are important in folklore. It is hoped that further studies will focus on values in Malay short stories.